Localized COUP‐TFII pDNA Delivery Modulates Stem/Progenitor Cell Differentiation to Enhance Endothelialization and Inhibit Calcification of Decellularized Allografts - Mengmeng Xing; Fei Wang; Ruowen Chu; He Wang; Yuyao Sun; Meng Qian; Huan Jiang; Adam C. Midgley; Guohao Dai; Qiang Zhao (Advanced Science)
Abstract Decellularized allografts have emerged as promising candidates for vascular bypass grafting, owing to their inherent bioactivity and minimal immunogenicity. However, graft failure that results from suboptimal regeneration and pathological remodeling has hindered their clinical adoption. Recent advances in vascular biology highlight the pivotal role of COUP‐TFII in orchestrating endothelial identity, angiogenesis, safeguarding against atherosclerosis, and mitigating vascular calcification. Here, plasmid DNA (pDNA) encoding COUP‐TFII is incorporated into decellularized allografts to realize localized delivery. Comprehensive in vitro investigation complemented by a bone marrow transplantation model on genetic‐lineage‐tracing mouse revealed the underlying mechanisms of COUP‐TFII in regulating vascular regeneration and remodeling. COUP‐TFII augmented endothelialization and inhibited calcification in decellularized allografts by modulating the Ang1/Tie2/PI3K/AKT signaling pathway that dictates the fate of Sca‐1+ stem/progenitor cells. Heparin‐polyethyleneimine nanoparticles (HEPI) are prepared as COUP‐TFII pDNA nanocarriers (COUP‐TFII@HPEI) and used to modify decellularized allografts, achieving long‐term and stable overexpression of COUP‐TFII. Functionalized grafts are evaluated in rat abdominal artery replacement models, demonstrating enhanced neo‐artery regeneration without calcification. The study provides an effective strategy to enhance the applicability of decellularized allograft and illustrates their translational prospects for vascular bypass grafting.